La percepción de la incursión de las TIC en el aula desde la perspectiva de los estudiantes universitarios - Hidalgo Cajo, Byron Geovanny (2018)
The information and communications technology (ICT) have impressively integrated into daily life, from this perspective we want to know its presence and impact on the teaching-learning process. To determine the use and application of ICT in the classroom and their influence on the teaching-learning process from the perception of students and undergraduate university teachers. The research is documentary and field, the universe or population consisted of 82 students and 3 teachers, data collection was the questionnaire. one descriptive and inferential statistical analysis was performed A very low percentage of teachers use ICT in the teaching-learning process of biostatistics, however students strongly believe that the incursion of them will have a positive impact on the educational process as verified the hypothesis by statistical . In biostatistics, it is rare use of ICT in the classroom so that students develop cognitive skills feebly, generation of intuitive ideas through trial and error generating new knowledge.